Análise e expressão de genes de PKS II e de carboidrases provenientes de bibliotecas metagenômicas - Gomes, Elisângela Soares [UNESP] (2015)
The Clone metagenomic B5pl37 (insert of 23kb length) was obtained by a PCR prospect for gene set Polyketide Synthases type II (PKSII) in a library cosmidial eucalyptus grove soil sample (SE). The PKSII are responsible for producing many bioactive molecules, among which the antibiotics were noticeable. Part of the sequence of the insert (27-43% coverage) showed similarity of 77-78% with bacteria Streptomycetaceae family (BLASTN tool, Genbank). In PKS II gene annotation was possible to identify genes related to the degradation of lignocellulosic important compounds for the production of second generation biofuel (2G): A β-glucosidase, a cellulose and a Multicopper oxidase (MCO). Considering the industrial importance of these genes, this study aimed to characterize in silico and in vitro /in vivo thereof. The in silico analyzes helped identify the architecture of the active site (protein structure obtained by homology) and enzyme families (based on phenetic groups with sequences of known enzyme activity). The in vitro / vivo experiments were performed in pET28a expression vector in Escherichia coli for cellulase (E. coli strains BL21; Artics and C41) and β-glucosidase (E. coli BL21), while the gene MCO in vitro synthesis for a subsequent study it was submitted. We had done the kinetic characterization of β- glucosidase (best performance in the expression and purification), which obtained the catalytic parameters: Vmax 0.79 uM / min; km from 0.46 mM. The respective temperature and the pH optimum for the enzyme was 37 ° C and pH7-7,5; and the enzyme was able to maintain an activity above 80% at a pH of 6.5-8.0 and temperature range 35-40 ° C. With respect to PKSII, the preparatory processes have been started to insert the expression in the same host specialized for expression of Streptomyces coelicolor antibiotic M1152 (courtesy of Juan P. Gomez-Escribano, John Innes Centre, Norwich, UK). Cosmidial exchange vector was carried out ...